A formação de uma comunidade de leitores - Pillon, Samariene Lucia Lopes (2007)
This work has as objective to analyze the formation of a readers’ community, through the analysis of an opinion article and the letters written in response to it. The corpus of the study consists of four Veja magazine columns written by Diogo Mainardi and of eleven readers’ letters addressed to him as responses. Beginning with the definition of motivation, by Meurer (1997), the analysis takes place concerning the appraisal theory precepts, by Martin & White (2005), and also the ethos conception, organized by Amossy (2005). Throughout the study, there is a belief on the possibility of applying the systems of genres, by Bazerman (2005), which points out to a regular sequence generated by a source-text (column) followed by others (in favor and against letters). The appraisal theory has been used to evaluate the language of each text, through the application of engagement and attitude strategies which are graded. Based on these categories, feelings and emotional reactions are analyzed, value assessments are done, and voices can be recognized within the expressions around any given question. It is our purpose to check how the alignment of these readers takes place in value communities. To do so, the observation of the genres system is intended. The production framework of these texts has been established since the discursive practice definition, by Fairclough (2001) and also from a social background, by Halliday (1989). Concerning the attitude evaluation marks, a prevalence of assessments could be observed, followed by approval and affection manifestations, the latter in smaller number. To what concerns the means of grading the evaluative anifestations, a high level of commitment by the writer has been verified in most of the opinion articles and reader’s letters. Considering the engagement process, there has been a predominance of the heteroglossy, within a large occurrence of dialogic contraction. The observation of the texts has confirmed the formation of a readers’ community hypothesis, arranged by people who read for admiration, others who seem to be curious, many others who feel challenged, shocked by polemic issues that many times cause awkwardness: all readers, as to show agreement or disagreement or to criticize. Based on the earlier observations, there is a tendency to believe that the ethos established by Diogo Mainardi in his texts could be the motivation to the formation of this community